Morphological, physiological and anatomical traits in durum wheat (Triticum durum Desf.) as affected by semi-arid conditions - Ali, Arous; Zemour, Kamel; Mehdeb, Djamila; Labdelli , Amina; Zemour , Hafidh; Chouhim , Kada Mohamed Amine; Adda , Ahmed; Belkhoudja , Moulay (Journal of Agriculture and Applied Biology, 2024)
Durum wheat (Triticum durum Desf.) is one of Algeria's primary cereal crops. Although the areas reserved for this species are estimated at approximately 40%, the production remains low to meet national grain requirements. This shortfall is primarily due to the impact of biotic and abiotic stresses, particularly drought, which significantly limit wheat yields. For that, this study assessed the behavior of five genotypes of durum wheat (Waha, Acsad1361, Vitron, Oued Zenati and Langlois) under water stress conditions. The experiment was carried out in Tiaret (Western Algeria). The studied parameters are morpho-physiological and anatomical of the flag leaf. The obtained results showed that the water deficit greatly affected the dimensions of the plant and triggered a decrease in the water content. Structural modifications due to cellular resizing of the structural constituents of the last leaf, reflected by variations in the rate of the outer epidermal wall thickness and reductions of leaf mesophiles. These modifications remain effective in maintaining the hydration of the aerial part by limiting water loss and increasing the hydraulic resistance of the leaves. According to this study, it seems that an inter-varietal difference has been highlighted. However, a genetic cross is recommended to combine the maximum number of resistant genes into a single variety. This strategy is considered as an effective solution for mitigating the effects of abiotic stresses, especially in semi-arid regions.